Literatur Review: Impact of Land Clearing for Palm Oil by Burning on Carbon Releases and Wildlife in Indonesia - Girsang, Sahat Raja Marigo; Has, Dini Hardiani; Daulay, Auliya Putra; Sukartara, Nirwansyah (Jurnal Biologi Tropis, 2024)
Fires on palm oil plantations always occur in Indonesia, although they have decreased from 2015 to 2020. This happens because fires are a fast and easy way to clear and clear land. Fires in palm oil plantations can damage the environment and wildlife.  Knowing the impact on the environment and animals, this article searches for and collects the results of previous research using traditional literature review methods. The literature review results show that oil palm was initially an ornamental plant brought from Africa, then cultivated in the Bogor Botanical Gardens. Successful cultivation is then developed into plantation crops that have the potential to be widely cultivated in Indonesia. This causes an increase in the need for land to cultivate these plants. This increase in land demand causes fires to occur in Indonesia which impacts the release of carbon and wildlife. Carbon released from vegetation fires causes air pollution which results in environmental damage. These fires can also harm wildlife due to loss of habitat and food sources. To reduce the impact of fires, recommendations are given to increase CPO production without having to open new land, which can potentially increase forest and land fires. The recommended method is a partnership with oil palm farmers. This can meet CPO production needs for local and international markets without having to open new concessions. This method can also be used as an alternative to help oil palm farmers manage crops and improve the community's economy.